Structure-activity relationship study at the 3 '-N-position of paclitaxel: Synthesis and biological evaluation of 3 '-N-acyl-paclitaxel analogues - Roh, EJ; Kim, D; Lee, CO; Choi, SU; Song, CE (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
A series of 3'-N-acyl-paclitaxel analogues la-v were synthesized and their cytotoxicities in vitro against several human tumor cell lines examined. It has been shown that distinct correlation between activity and N-acyl-substituent. The appropriate size of N-acyl group was indispensable for cytotoxicity, and moreover, the presence of beta-substituted conjugated double and triple bond to N-carbonyl generally resulted in increase of cytotoxicities. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: ANTITUMOR AGENTS; TAXOL